Influence of atmospheric dust deposition on sinking particle flux in the northwest Pacific - Kim, Hyung Jeek; Kim, Dongseon; Park, Young-Gyu; Park, Jong-Yeon; Choi, Ki-Young; Park, Joon Sang; An, Sung Min; Kwon, Kyungman; Noh, Jae Hoon; Hwang, Jeomshik (Frontiers in Marine Science, 2023)
We examined the flux and composition of sinking particles collected at a water depth of 800 m in the northwest Pacific from November 2017 to August 2018 to assess the impact of dust deposition on organic carbon export. The fluxes of total particulate matter and particulate organic carbon averaged over the study period were 88 ± 63 mg m-2 d-1 and 9.0 ± 5.8 mg m−2 d−1, respectively. Biogenic particles accounted for 82% of the sinking particles, on average. There were two notable pulses in the particle fluxes of both biogenic and lithogenic material in February and May 2018. These flux peaks were decoupled from net primary production in the surface waters but coincided with intervals of high rates of atmospheric dust deposition. The biogenic component of the two peaks was dominated by two different phytoplankton communities, which may have influenced carbon export efficiency. Correlations between the sinking particle flux and the lithogenic flux are found at several locations in the northwest Pacific, implying that East Asian dust deposition has a prevalent influence on the biological pump. Attention should be paid to the effects of changes in the continental dust supply to the oceans on oceanic carbon export.